2019
DOI: 10.14710/jksa.22.5.173-178
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Loloh (Traditional Balinese Medicine) Decoction Water and Squeeze Water of betel Leaf against Bacteria Streptococcus pyogenes causes of sore throat

Abstract: Sore throat is a respiratory infection caused by a bacterial infection of Streptococcus pyogenes. Betel leaf is used for loloh (traditional medicine) which has antimicrobial activity. The purpose of this study was to determine the content of active compounds and the antibacterial activity of the boiled water and juice of betel leaf against Streptococcus pyogenes. Explorative research using GC-MS method was used to identify and determine the abundance (content) of active compounds from loloh while the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Betel leaf contains vitamins (A, B, and C), as well as minerals (Fe and Zn), which have been demonstrated to have key roles in supporting the human immune system, and reducing the risk of infections oral disease, and COVID-19, the reaction scheme is depicted in Figure 2. 25, 33 Studies have shown that the immune-stimulating vitamin zinc may lower viral multiplication and promote immunological responses. Prophylactic may offer an additional defense while eating zinc (within the advised upper safety limits).…”
Section: Immunomodulatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Betel leaf contains vitamins (A, B, and C), as well as minerals (Fe and Zn), which have been demonstrated to have key roles in supporting the human immune system, and reducing the risk of infections oral disease, and COVID-19, the reaction scheme is depicted in Figure 2. 25, 33 Studies have shown that the immune-stimulating vitamin zinc may lower viral multiplication and promote immunological responses. Prophylactic may offer an additional defense while eating zinc (within the advised upper safety limits).…”
Section: Immunomodulatory Activitymentioning
confidence: 99%
“…29 Iron deficiency induces thymus atrophy, reducing the output of naive T lymphocytes, and has multiple effects on immune function in humans. 33 A summary of the reaction scheme is depicted in Figure 2.…”
Section: Immunomodulatory Activitymentioning
confidence: 99%
“…Ekstrak etanol daun sirih mampu menghambat pertumbuhan Staphylococcus aureus penyebab konjungtivitis (Lubis, Marlisa, & Wahyuni, 2020) dan Streptococcus mutans (Owu, Fatimawali, & Jayanti, 2020). Infusa daun sirih mampu menghambat pertumbuhan bakteri Streptococcus pyogenes (Sumarya, Suarda, & Sudaryati, 2019;(Amanda, Mastra, & Sudarmanto, 2018) dan Escherichia coli (Hamzah, Septilapani, & Frimayanti, 2021) Infusa daun sirih dapat menghambat pertumbuhan Staphyloccocus aureus (Wirahmi, Triansyah, Amri, & Masrijal, 2021).…”
Section: Introductionunclassified